Compressive and flexural properties of functionally graded fly ash cenosphere–epoxy resin syntactic foams. Issue 4 (27th March 2014) - Doddamani, Mrityunjay; Kishore,; Shunmugasamy, Vasanth Chakravarthy; Gupta, Nikhil; Vijayakumar, H.B.
Abstract : The present study focuses on developing functionally graded syntactic foams (FGSFs) based on a layered co‐curing technique. The FGSFs were characterized for compressive and flexural properties and compared with plain syntactic foams. The results showed that the specific compressive modulus was 3–67% higher in FGSFs compared to plain syntactic foams. FGSF exhibited 5–34% and 34–87% higher specific modulus and strength, respectively in flexural mode. The microscopic examinations of comparative responses of the filler and matrix to deformation suggest that the failure is dominated by the matrix. The gradient in the composition of syntactic foams helps in effectively distributing the stress throughout the microstructure and results in improved mechanical performance of syntactic foams. From the microscopy studies, it is evident that, the failure mechanism in the FGSF under flexural loading is governed by a crack that initiated on the tensile side of the specimen and propagated through the thickness to cause complete fracture. The microscopic observations further clearly demonstrate the existence of seamless interfaces between the layers and a clear difference in the cenosphere concentration across the interface, affirming the gradation in the prepared samples. The results show that appropriate compositions of FGSFs can be selected to develop materials with improved mechanical performance. POLYM. COMPOS., 36:685–693, 2015. © 2014 Society of Plastics Engineers